Some Considerations about De Facto Governments and Constitutional Validity - Belaúnde López de Romaña, Javier de (1974)
In 1968, the Revolutionary Government of the Armed Forces took control and introduced changes that violated the 1933 Political Constitution of Peru. From that moment on, a debate has been generated on the validity of the Constitution. The purpose of this paper is to analyze the legal considerations surrounding de facto governments and the problem of constitutional validity. In this direction, the concepts of constitutionalism and the effects of de facto governments on the legal system are under investigation. This framework allows the evaluation of the mutations and the identification of the legal changes introduced by coups d'état. It is concluded that in order to verify the effective application of constitutional law, as in the case of de facto governments, it is of the utmost importance to analyze it in its historical, social and economic context.